Plans and specifications for the installation of a 300 kilo-watt unit in the Manhattan Power Station. - Eaton, Gio R.; Hoffman, G. Leon (My University, 1908)
Introduction: Excavation. The excavation is to be 3 feet wide and 3 feet deep. Foundation. The foundation is to built of good stone laid in Portland Cement Mortar. Walls. The walls are made to be of rough stone, the same as old walls. Thickness 30 inches. The east wall will be the new boiler room wall.
Citation: Eaton, Gio R. and Hoffman, G. Leon. Plans and specifications for the installation of a 300 kilo-watt unit in the Manhattan Power Station. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Architecture; Blueprints; Power; Kansas; Graduating theses; Senior theses; Theses